Sertifikasi Halal Produk Untuk Peningkatan Daya Saing Usaha Pada UMK di Desa Ciseeng - Ismail, Verni Yuliaty; Annisa, Intan Tri; Roswiem, Anna P (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
The Muslim population in Indonesia represents a large potential consumer base for food products. Obtaining a halal product certificate adds value for businesses, enabling them to produce and sell halal products that align with the consumption values of Muslim consumers. Additionally, the government mandates that food and beverage products from MSMEs (Micro, Small, and Medium Enterprises) must obtain halal certificates. Ciseeng Village, located in Bogor Regency, West Java, is home to many MSMEs that produce food, yet relatively few have halal product certificates. The aim of this Community Service Activity is to help develop the potential of MSMEs in the Ciseeng area by increasing the competitiveness of their food product businesses. One key effort in this development is the issuance of halal certificates for MSME food products. A major obstacle is the lack of knowledge among MSMEs about the criteria for halal products and the procedures for obtaining halal certificates. To address this, the YARSI University Community Service Institute offers education on halal products, workshops on the self-declaration process for halal certification, and direct assistance with registration on the Halal Information System (SIHALAL). As a result of this activity, there was an increase in understanding of halal products, and of the 15 MSMEs that registered for halal product certification, 8 successfully obtained halal certificates from BPJPH.